Editorial resistance: countercultural genealogy of publication practices in Argentine prisons - Rubin, María José (2022)
This article proposes to address the editorial practice in Argentine prisons in recent years through the study of some cases in relation to countercultural publishing practices such as the punk fanzines and the underground magazines edited during the 1970s and 1980s, coinciding with the last dictatorship and the immediate post-dictatorship in the country. An interpretive reading of six publications will be carried out from the interdisciplinary field of Book and Publishing Studies, observing in books, magazines and other formats the material marks of an editorial practice that is proposed as an aesthetic and political alternative to the logics of the market and its link with the great hegemonic powers.